Evaluation of spring barley cultivars released in Belarus under the environmental conditions of the Northern Trans-Urals - M. N. Fomina; Yu. S. Ivanova; M. V. Bragina; O. N. Kovaleva (Труды по прикладной ботанике, генетике и селекции)
Background. Studying the genetic diversity of ex situ barley accessions under contrasting environmental conditions (humid with a lack of heat, favorable, arid, etc.) makes it possible to assess them according to the duration of the growing season, resistance to lodging, potential productivity, drought resistance, grain quality, and environmental plasticity. Materials and methods. The results of an 8-year trial (2016–2023) of 11 spring barley accessions of Belarusian origin in the northern forest-steppe zone of Tyumen Province are presented. The experiments followed the protocols adopted for the state variety trials. An SKS-6-10 seeder was used for sowing, the plot area was 5 m2 , and cv. ʻAbalakʼ served as the reference. The seeding rate was 550 viable seeds per 1 m2 . Results. A majority of the studied accessions matured later than the medium-ripening reference cultivar. Weather conditions during the growing season in the Northern Trans-Urals had a decisive effect on the harvest formation, protein content and starch content in barley grain (74.6%, 70.8% and 81.8%, respectively). The effect of the genotype on these indicators was 7.9%, 17.5% and 6.2%, respectively. Starch content also depended on the genotype × environment interaction (9.7%). Fat content was almost equally affected by the genotype (25.1%) and the environment (26.7%). The genotype × environment interaction was more significant (31.2%). Conclusion. The following sources were identified among the tested cultivars: ‘Vodar’ (high yield, drought tolerance, etc.); ‘Magutny’ (high yield, and environmental plasticity); ‘Khago’ (large grain, low hull content, and increased protein and starch content levels); ‘Lipen’ (high test weight, increased starch content, and environmental plasticity); ‘Fobos’ (drought tolerance, and increased protein content); ‘Dublet’ (lodging resistance, and increased protein content); ‘Taler’ (reduced protein content, and environmental plasticity); ‘Pospekh’ (reduced protein content).